Clinical Effectiveness of Intraoperative Tranexamic Acid Use in Shoulder Surgery: A Systematic Review and Meta-analysis. Issue 11 (September 2021) - Hartland, Alexander W.; Teoh, Kar H.; Rashid, Mustafa S.
Background: Tranexamic acid (TXA) is widely used across surgical specialties to reduce perioperative bleeding. It has been shown to be effective in spinal surgery and lower limb arthroplasty. Among all languages, there are no systematic reviews or meta-analyses investigating its clinical effectiveness for all types of shoulder surgery. Purpose: To investigate the clinical effectiveness of TXA in all types of shoulder surgery, including open and arthroscopic procedures. To investigate the effect of TXA on bleeding and non–bleeding-related outcomes. Study Design: Systematic review and meta-analysis. Methods: A protocol for the study was designed and registered with PROSPERO (CRD42020185482). The literature search included the MEDLINE, Embase, PsycINFO, and Cochrane Library databases. All randomized controlled trials evaluating the use of TXA against placebo, in all types of shoulder surgery, were included. Assessments were undertaken for risk of bias and certainty of evidence. The primary outcome was total blood loss. Secondary outcomes included those not directly related to bleeding. Data from comparable outcomes were pooled and analyzed quantitatively or descriptively, as appropriate. Results: Eight randomized controlled trials were included in the systematic review, and data from 7 of these studies were pooled in the meta-analysis. Pooled analysis demonstrated a significant reduction in 2 of 3 outcomes measuring perioperative bleeding with TXA compared with controls: estimated total blood loss (mean difference, −209.66 mL; 95% CI, −389.11 to −30.21; P = .02) and postoperative blood loss as measured by drain output (mean difference, −84.8 mL; 95% CI, −140.04 to −29.56; P = .003). Hemoglobin reduction was reduced but not statistically significant (mean difference, –0.33 g/dL; 95% CI −0.69 to 0.03; P = .07). This result became significant with sensitivity analysis excluding arthroscopic procedures. Conclusion: This systematic review and meta-analysis indicated that TXA was effective in reducing blood loss in shoulder surgery. Larger randomized controlled trials with low risk of bias for specific surgical shoulder procedures are required. Clinical Relevance: TXA can be used across shoulder surgery to reduced perioperative blood loss. The use of TXA may have other beneficial features, including reduced postoperative pain and reduced operative time.